Optimization-Driven Evaluation of Multilayer Graphene Concrete: Strength Enhancement and Carbon Reduction Through Experimental and Mathematical Integration - Shabbir, Kamran; Idrees, Maria; Masood, Rehan; Sammad, Muhammad Hassan (Journal of composites science, 2025)
The integration of nanoengineered materials into concrete systems has emerged as a promising strategy for enhancing structural performance and sustainability. This study presents a hybrid experimental-analytical investigation into the use of multilayer graphene as a smart admixture in high-performance concrete. The research combines mechanical testing, microstructural characterization, and a multi-objective optimization model to determine the optimal graphene dosage that maximizes strength gains while minimizing carbon emissions. Concrete specimens incorporating multilayer graphene (ranging from 0.01% to 0.10% by weight of cement) were tested over 7 to 90 days for compressive, tensile, and flexural strengths. Simultaneously, X-ray diffraction, scanning electron microscopy, and energy-dispersive X-ray analyses revealed crystallinity enhancement, pore densification, and favorable elemental redistribution due to graphene inclusion. A normalized composite objective function was formulated to balance three maximization targets—compressive, tensile, and flexural strength—and one minimization goal—carbon emission. The highest objective score (Z = 1.047) was achieved at 0.10% graphene dosage, indicating the optimal balance of strength performance and environmental efficiency. This dual-framework study not only confirms graphene’s reinforcing effects experimentally but also validates the 0.10% dosage through mathematical scoring. The outcomes position of multilayer graphene as a powerful additive for high-strength, low-carbon concrete, especially suited for infrastructure in hot and arid environments. The proposed optimization approach provides a scalable pathway for performance-based graphene dosing in future innovative concrete formulations.